DEVELOPMENT OF LKPD BASED ON SETS-PJBL TO TRAIN CRITICAL THINKING SKILLS OF STUDENTS - Muhammad Akhsan Arif; Fitri Nur Hikmah (International Conference on Education, Science, Technology and Health (ICONESTH), 2024)
This study aims to produce SETS-PjBL-based Learner Worksheets (LKPD) and train students' critical thinking skills. The Research and Development (RnD) method was used in this study through the RnD stage of the ADDIE Model with 34 participants of class XI 4 SMAN 4 Banjarmasin and the subject of SETS-PjBL-based LKPD. The results of this study showed: 1) The experts' validity of the SETS-PjBL-based LKPD is categorised as very good with a percentage of 94%. 2) The developed LKPD received a good response from students with a percentage of 74.90%. 3) The critical thinking skills of students obtained from the overall observation results are good with a percentage of 79.46%.